African indigenous vegetable marketing: examining the influence of socio-economic factors and market patterns in Tanzania - Isaac Kazungu (Cogent Business & Management, 2024)
While most studies on African Indigenous Vegetables (AIV) focused on their nutritional values, household income and consumer attitudes, little has been documented on their marketing patterns. This study examines the influence of socio-economic factors and market patterns on AIV marketing among smallholder farmers in Arusha Tanzania. The study applied a cross-sectional design, in which a structured questionnaire was adopted to capture information from 288 sampled AIV producers. The Cobb Douglas (Double Log) regression model was employed during data analysis. Findings indicate that smallholder farmers' marital status, education level, and household size are positively and significantly influencing the marketing of these vegetables. Also, a positive and significant effect of smallholder farmers' trade experience, marketing infrastructure, AIV varieties, marketing information and market channel was observed. The findings of this study extend the application of market orientation theory and resource-based theory in the context of AIV marketing. This study provides a marketing framework for policymakers and smallholder vegetable farmers on better marketing strategies for active involvement in vegetable markets. This study contributes to the body of knowledge on the need for policy reforms to enhance AIV marketing patterns in developing economies. Also, the findings of this study have both practical and policy implications.
Keywords: 650; Smallholder farmers; marketing; African indigenous vegetable; market patterns; Arusha and Tanzania